Development and validation of stability indicating HPTLC method for estimation of dextromethorphan hydrobromide - Gandhi, Santosh V; Dyandyan, Shubhangi K. (Journal of Applied Pharmaceutical Research, 2017)
A simple, sensitive and accurate stability indicating HPTLC method has been developed and validated for estimation of Dextromethorphan hydrobromide in bulk and pharmaceutical dosage form. The drug was spotted on precoated silica gel 60 F254 aluminum plates using Toluene: Methanol: Triethylamine (8.5:1:0.5 v/v/v) as mobile phase. The retention factor (Rf) was found to be 0.60Â±1.92. The detection of band was carried at 225 nm. The drug was subjected to different stress conditions like acid, base, neutral hydrolysis, oxidation, thermal degradation and photolysis. The method was successfully validated according to ICH guidelines Q2 (R1). The data of linear regression analysis indicated a good linear relationship over the concentration range of 2000-20000 ng/band with correlation coefficient 0.991. The method found to be accurate as results of the recovery studies are close to 100 %. The developed method was found to be simple, sensitive, selective, accurate and repeatable for analysis of and can be adopted for routine analysis of drug in bulk and pharmaceutical dosage form.